Formation of economic and legal measures for the development of the market of intellectual property objects - Maslak, M. V.; Pererva, P. G. (ПП "Технологічний Центр", 2023)
The problems of intellectual property market development have been investigated. It is proved that without the successful functioning of this market it is impossible to ensure the innovative development of the country. The characteristics of the intellectual property market, as well as the factors restraining its development, have been determined. The most important of them are significant volumes of outflow of Ukrainian scientists to foreign countries, low quality of Ukrainian patents, high level of counterfeiting and piracy, corruption pressure on the development and use of intellectual property, insufficient level of material support, etc. Therefore, the purpose of this study is to develop measures to strengthen the factors that contribute to the development of the intellectual property market and reduce the negative impact of factors on the Ukrainian technological market. To achieve the goal, it is proposed to introduce organizational and legal measures to improve the working conditions of employees of the main scientific institution of the country, the National Academy of Sciences (NAS) of Ukraine, the institutes of which produce most intellectual developments, as well as to form special financial and material mechanisms to support innovation at the expense of budget funds. Using the example of reforming the institutes of NAS, according to the proposed measures, proposals have been formed to preserve scientific personnel, intensify the cooperation of scientific institutions with business, built on the interest of all parties in the field of technology commercialization. Counteraction to counterfeiting is proposed to be carried out taking into account a more accurate calculation of the commercial risks to which business entities are exposed in the manufacture and use of innovations. It is recommended to strengthen the level of legal protection of exclusive rights. Legislative initiatives on the development of the intellectual property market have been formed, which relate to changes in patent legislation regarding utility models and bringing it to EU conditions.

Досліджено проблеми розвитку ринку інтелектуальної власності. Доведено, що без успішного функціонування цього ринку неможливо забезпечити інноваційний розвиток країни. Визначено характеристики ринку інтелектуальної власності, а також фактори стримування його розвитку. Найбільш важливими з них є значні обсяги відтоку українських вчених в зарубіжні країни, низька якість українських патентів, високий рівень контрафакції та піратства, корупційний тиск на розробки та використання інтелектуальної власності, недостатній рівень матеріальної підтримки та ін. Тому метою даного дослідження є розробка заходів щодо посилення факторів, які сприяють розвитку ринку інтелектуальної власності та зменшення негативного впливу наявних на українському технологічному ринку чинників. Для досягнення мети запропоновано ввести організаційні та правові заходи щодо покращення умов роботи співробітників головної наукової установи країни, якою є Національна академія наук (НАН) України, від інститутів якої і виходить більшість інтелектуальних розробок, за рахунок бюджетних коштів формувати спеціальні фінансово-матеріальні механізми підтримки інноваційної діяльності. На прикладі реформування інститутів НАН, згідно пропонованих заходів, сформовано пропозиції по збереженню наукових кадрів, активізації співпраці наукових установ з бізнесом, побудованій на інтересі всіх сторін в сфері комерціалізації технологій. Протидію контрафакту та фальсифікату пропонується здійснювати з урахуванням більш точного розрахунку комерційних ризиків, яким піддаються суб’єкти господарювання при виготовленні та використанні інновацій. Рекомендовано посилити рівень правової охорони виключних прав. Сформовано законодавчі ініціативи щодо розвитку ринку інтелектуальної власності, які стосуються зміни патентного законодавства відносно корисних моделей та приведення його до умов ЄС.
Формування економіко-правових заходів щодо розвитку ринку об’єктів інтелектуальної власності
Keywords: intellectual property; market; development; legislation; economy; financing; counterfeiting; franchising; інтелектуальна власність; ринок; розвиток; законодавство; економіка; фінансування; контрафакт; франчайзинг